Embracing Students’ Diverse Learning Styles in English Classroom Activities - Dewi Pujiantini (Universitas Negeri Yogyakarta, 2022)
Students are different in many respects due to their characteristics. The characteristics show that Individual Differences (IDs) are common among students. In the second language learning context, one of the key IDs is learning styles. Students’ learning styles are identified from their preferred ways for acquiring information, knowledge, and skills. Students’ learning styles should be recognized and taken into account by English teachers in planning the instructional design and conducting classroom activities to create meaningful and engaging learning activities to achieve effective learning outcomes. However, to my reflection and observation in my own area, most EFL teachers pay very little attention, if any at all, to matters related to learning styles. Many teachers indeed employ a ‘one size fits all’ teaching method. However, a large number of students and limited time allocation create an obstacle for teachers in dealing with students’ different learning styles. There should be a teaching model to accommodate students’ different learning styles in the instructional design and learning process. Therefore, this paper is aimed at proposing a model of teaching that presents some steps to be taken by teachers as an effort to accommodate students’ different learning styles that focus on achieving successful English language learning and keeping the value of students’ different learning styles. Keywords: language learning, students’ learning styles, learning process, learning activities, teaching model